Impact of antitumour necrosis factor therapy on surgery in inflammatory bowel disease: a population-based study - Richard C G Pollok; Rebecca Cannings-John; Philip Harborne; A Barney Hawthorne; Bradley Arms-Williams; Alexander Berry; Anjali Trivedi (BMJ Open Gastroenterology)
Objective It is unclear whether widespread use of biologics is reducing inflammatory bowel disease (IBD) surgical resection rates. We designed a population-based study evaluating the impact of early antitumour necrosis factor (TNF) on surgical resection rates up to 5 years from diagnosis.Design We evaluated all patients with IBD diagnosed in Cardiff, Wales 2005–2016. The primary measure was the impact of early (within 1 year of diagnosis) sustained (at least 3 months) anti-TNF compared with no therapy on surgical resection rates. Baseline factors were used to balance groups by propensity scores, with inverse probability of treatment weighting (IPTW) methodology and removing immortal time bias. Crohn’s disease (CD) and ulcerative colitis (UC) with IBD unclassified (IBD-U) (excluding those with proctitis) were analysed.Results 1250 patients were studied. For CD, early sustained anti-TNF therapy was associated with a reduced likelihood of resection compared with no treatment (IPTW HR 0.29 (95% CI 0.13 to 0.65), p=0.003). In UC including IBD-U (excluding proctitis), there was an increase in the risk of colectomy for the early sustained anti-TNF group compared with no treatment (IPTW HR 4.6 (95% CI 1.9 to 10), p=0.001).Conclusions Early sustained use of anti-TNF therapy is associated with reduced surgical resection rates in CD, but not in UC where there was a paradoxical increased surgery rate. This was because baseline clinical factors were less predictive of colectomy than anti-TNF usage. These data support the use of early introduction of anti-TNF therapy in CD whereas benefit in UC cannot be assessed by this methodology.